1999
DOI: 10.1542/peds.103.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pediatric Trauma Response Team on Emergency Department Treatment Time and Mortality of Pediatric Trauma Victims

Abstract: Before creation of the trauma team, relevant specialists were individually called to the ED for patient evaluation. When a formal trauma response team was organized, time required for ED treatment of severe trauma was decreased, and survival was better than predicted compared with the reference Major Trauma Outcome Study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 21 publications
2
41
0
2
Order By: Relevance
“…Haller and Beaver [6] demonstrated that a management system improved pediatric outcomes in patients with life-threatening injuries. In addition, Vernon et al [7] reported that patients treated by a trauma team had shorter ED time, ED to computed tomographic imaging time, ED to operating room time, and improved survival when compared with the control group where specialists were notified on an individual basis. Previous studies have shown that a TA system, with mobilizing different members of personnel, permits effective use of hospital resources.…”
Section: Discussionmentioning
confidence: 99%
“…Haller and Beaver [6] demonstrated that a management system improved pediatric outcomes in patients with life-threatening injuries. In addition, Vernon et al [7] reported that patients treated by a trauma team had shorter ED time, ED to computed tomographic imaging time, ED to operating room time, and improved survival when compared with the control group where specialists were notified on an individual basis. Previous studies have shown that a TA system, with mobilizing different members of personnel, permits effective use of hospital resources.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent study provides evidence that the trauma team approach is effective in reduction of time to definitive treatment and ultimately increase in survival. 3 Implicit in the trauma team concept is the use of criteria that, when met, trigger the assembly of the team in the receiving emergency department (ED). Similar to the goal of field triage guidelines, the goal is to quickly allocate limited resources to those who need them.…”
mentioning
confidence: 99%
“…3 In addition, the StatScan can provide a full body and cervical spine scan of a young child in just 10 s, it can be situated in the trauma room, does not require the patient to be transferred to another trolley to be scanned as it has an integrated docking resuscitation trolley and compared to conventional X-rays has an extremely low radiation dose. 1,2,9 This is particularly important for paediatric patients who are very susceptible to the adverse effects of radiation with increased rates of thyroid, breast, leukaemias and other cancers being reported. 6 This case illustrates that the StatScan is a highly efficient method for identifying increased ADI.…”
Section: Discussionmentioning
confidence: 99%